2019
DOI: 10.2174/1568026619666191105112800
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Dual Negative Allosteric Modulators of Group I mGluR Family: A Shape Based Screening, ADME Prediction, Induced Fit Docking and Molecular Dynamics Approach Against Neurodegenerative Diseases

Abstract: Background: Glutamate is the principal neurotransmitter in the human brain that exerts its effects through ionotropic glutamate receptors (iGluRs) and metabotropic glutamate receptors (mGluRs). The mGluRs are a class of C GPCRs that play a vital role in various neurobiological functions, mGluR1 and mGluR5 are the two receptors distributed throughout the brain involved in cognition, learning, memory, and other important neurological processes. Dysfunction of these receptors can cause neurodegenerative diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, more models should be constructed to cover more diverse chemical space if different shapes are available (Perez-Nueno and Ritchie, 2011 ), particularly for highly flexible proteins. Some studies using the shape-focused method have been reported in recent years (Reddy et al, 2013 ; Chen et al, 2015 ; Kumar et al, 2015 ; Prabhu and Singh, 2019 ). For example, Chen et al ( 2015 ) presented a shape-based virtual screening to find new cores for the design of acetylcholinesterase (AChE) inhibitors.…”
Section: In Silico Approachesmentioning
confidence: 99%
“…However, more models should be constructed to cover more diverse chemical space if different shapes are available (Perez-Nueno and Ritchie, 2011 ), particularly for highly flexible proteins. Some studies using the shape-focused method have been reported in recent years (Reddy et al, 2013 ; Chen et al, 2015 ; Kumar et al, 2015 ; Prabhu and Singh, 2019 ). For example, Chen et al ( 2015 ) presented a shape-based virtual screening to find new cores for the design of acetylcholinesterase (AChE) inhibitors.…”
Section: In Silico Approachesmentioning
confidence: 99%
“…In the drug development process, parameters such as absorption, distribution, metabolism, excretion, and toxicity (ADMET) must be assessed since they determine the potential effect of the compound under study. In this regard, molecular modeling allows the prediction of ADMET properties through the application of different approaches such as pharmacophore modelling, molecular docking, dynamic simulations, and quantum mechanics calculation 26–30 …”
Section: Virtual Compound Screening Approachmentioning
confidence: 99%
“…These characteristics will help with finding a novel targeting strategy to precisely regulate CTDSP1's activity. The field of drug designing has been rapidly advancing in recent decades, and many new state-ofthe-art technologies and methods have been discovered [20,[104][105][106][107][108][109][110][111][112][113][114]. Well rationalized structural information of receptor proteins and ligand chemicals is the essential requirement for drug designing.…”
Section: Challenges and Opportunities In Targeting Ctdsp1mentioning
confidence: 99%
“…Numerous software tools for protein-ligand dockings, such as Autodock, DOCK 4.0, GOLD, Flex-X, ICM, SLIDE, GLIDE, and DeepBindRG, were developed based on various scoring functions, including empirical, knowledge-based, and machine learning, and are summarized in Table 2 [50,[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130]. The field of drug designing has been rapidly advancing in recent decades, and many new state-of-the-art technologies and methods have been discovered [20,[104][105][106][107][108][109][110][111][112][113][114]. Well rationalized structural information of receptor proteins and ligand chemicals is the essential requirement for drug designing.…”
Section: Challenges and Opportunities In Targeting Ctdsp1mentioning
confidence: 99%
See 1 more Smart Citation